Occupational and residential radon exposure: a study in North-Western Greece - Patiris, D. L.; Ioannides, K. G.; Papachristodoulou, C. A. (HNPS Advances in Nuclear Physics, 2020)
Measurements of indoor radon concentrations were performed in 44 workplaces and 87 dwellings in the region of Epirus, north-western Greece, using electret and alpha-track detectors. Radon concentrations followed a log-normal distribution with an arithmetic mean of 92 Bq/m3 in workplaces and 86 Bq/m3 in dwellings. A mean annual effective dose of 0.64 and 1.63 mSv/y was estimated for occupational and residential exposure, respectively. The reported data contribute to the assessment of radon distribution and dose estimate at the national level.